Spatial assessment of the vulnerability of benthic communities to multiple stressors in the Yucatan Continental Shelf, Gulf of Mexico. (1st November 2019) - Ocaña, Frank A.; Pech, Daniel; Simões, Nuno; Hernández-Ávila, Iván
Abstract: Here, we show a spatially explicit assessment of the vulnerability of benthic communities from the Yucatan Continental Shelf (YCS) to multiple pressures: fishing activities, shipping traffic, storms and hurricanes, and marine acidification. The vulnerability index was obtained by combining benthic biological traits with exposure and sensitivity and recovery capacity; this was then represented in a spatially explicit model. Moreover, we estimated a cumulative vulnerability index using three different scenarios that were based on 1) equal weight for each vulnerability layer to each stressor, 2) results of expert consultation and 3) a linear reduction in the weight of the pressures. By comparing scenarios, the synergistic and antagonistic effects of the multiple stressors were determined. The main results showed that, independent of the considered scenario, approximately 90% of the YCS presented moderate to high vulnerability to cumulative pressures, while areas with high recovery and high potential impact on a particular stressor showed low or moderate vulnerability to the pressures. Meanwhile, areas classified as having medium impact levels and low recovery capacities of benthic fauna showed moderate to high vulnerability to the same threats. Our findings also showed that ship traffic and marine acidification were the threats that contributed to the greatest vulnerability. The paired comparison of scenarios allows for the identification of areas with higher probabilities of synergistic effects. No antagonistic effects were detected. Overall, our results constitute the first effort to understand the ecological status of the benthic communities of the YCS and their potential vulnerability to the multiple pressures they face. Highlights: Vulnerability assessment to multiple pressures identify areas with high potential impact. Marine traffic and ocean acidification are the main threats for the benthos. The inclusion of benthic recovery traits improves the vulnerability assessment. Synergistic and antagonistic impacts can be identified using pressures weighting scenarios.